Progress of research on the effect of implant surface nano-morphology on osteoblast adhesion - PENG Hanyu, LI Xiao (Kouqiang yixue)
Osteoblasts are the main functional cells of bone formation, and their adhesion to the implants is the premise of biological function. However, most of the common clinical implants are inert metals, which have some problems such as poor biological activity and lack of bone induction, which are not conducive to osteoblast adhesion, so it is often necessary to modify their surface. Nano-morphology is a hot topic in recent years, which refers to the topological structure of implant surface unit and size 1-100 nm, similar to extracellular matrix in structure, with many advantages such as enhanced hydrophilicity, superior biocompatibility and antibacterial properties. However, not all nano-morphologies are conducive to osteoblast adhesion. This paper reviews the adhesion process, common nano-surface structure and surface modification of osteoblasts on nano-surface, in order to provide reference for implant surface nano-modification and clinical application.